Dengue seroprevalence and force of primary infection in a representative population of urban dwelling Indonesian children. - Ari Prayitno; Anne-Frieda Taurel; Joshua Nealon; Hindra Irawan Satari; Mulya Rahma Karyanti; Rini Sekartini; Soedjatmiko Soedjatmiko; Hartono Gunardi; Bernie Endyarni Medise; R Tedjo Sasmono; James Mark Simmerman; Alain Bouckenooghe; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Indonesia reports the second highest dengue disease burden in the world; these data are from passive surveillance reports and are likely to be significant underestimates. Age-stratified seroprevalence data are relatively unbiased indicators of past exposure and allow understanding of transmission dynamics. METHODOLOGY/PRINCIPAL FINDINGS:To better understand dengue infection history and associated risk factors in Indonesia, a representative population-based cross-sectional dengue seroprevalence study was conducted in 1-18-year-old urban children. From October to November 2014, 3,210 children were enrolled from 30 geographically dispersed clusters. Serum samples were tested for anti-dengue IgG antibodies by indirect ELISA. A questionnaire investigated associations between dengue serologic status and household socio-demographic and behavioural factors. Overall, 3,194 samples were tested, giving an adjusted national seroprevalence in this urban population of 69.4% [95% CI: 64.4-74.3] (33.8% [95% CI: 26.4-41.2] in the 1-4-year-olds, 65.4% [95% CI: 69.1-71.7] in the 5-9-year-olds, 83.1% [95% CI: 77.1-89.0] in the 10-14-year-olds, and 89.0% [95% CI: 83.9-94.1] in the 15-18-year-olds). The median age of seroconversion estimated through a linear model was 4.8 years. Using a catalytic model and considering a constant force of infection we estimated 13.1% of children experience a primary infection per year. Through a hierarchical logistic multivariate model, the subject's age group (1-4 vs 5-9 OR = 4.25; 1-4 vs. 10-14 OR = 12.60; and 1-4 vs 15-18 OR = 21.87; p<0.0001) and the number of cases diagnosed in the household since the subject was born (p = 0.0004) remained associated with dengue serological status. CONCLUSIONS/SIGNIFICANCE:This is the first dengue seroprevalence study in Indonesia that is targeting a representative sample of the urban paediatric population. This study revealed that more than 80% of children aged 10 years or over have experienced dengue infection at least once. Prospective incidence studies would likely reveal dengue burdens far in excess of reported incidence rates.